2008
DOI: 10.1097/wnr.0b013e3283036e5e
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain acetylcholine and glutamate receptors modulate accumbal dopamine release

Abstract: This study determined the role of ventral tegmental area acetylcholine and glutamate receptors in modulating laterodorsal tegmentum stimulation-evoked dopamine efflux in the nucleus accumbens. Rapid changes in dopamine oxidation current were measured at carbon fiber microelectrodes using fixed potential amperometry in urethane anesthetized male mice. Intraventral tegmental area infusions of the muscarinic acetylcholine receptor antagonist scopolamine, the nicotinic acetylcholine receptor antagonist mecamylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Fixed potential amperometry coupled with carbon fiber microelectrodes has been confirmed as a valid technique for real-time monitoring of DA oxidation current evoked by brief electrical stimulation of ascending mesoaccumbens dopaminergic projections (Benoit-Marand et al 2000;Dugast et al 1994;Lester et al 2008Lester et al , 2009Schönfuß et al 2001;Suaud-Chagny 2004). Confirmation of the chemical specificity of our amperometric measurements has been provided by previous studies (e.g., Lee et al 2006;Mittleman et al 2008), showing that systemic administration of the selective DA reuptake inhibitor nomifensine significantly increases electrical stimulation-evoked DA oxidation current and delays recovery to prestimulation baseline levels.…”
Section: Da Functional Dynamicsmentioning
confidence: 69%
“…Fixed potential amperometry coupled with carbon fiber microelectrodes has been confirmed as a valid technique for real-time monitoring of DA oxidation current evoked by brief electrical stimulation of ascending mesoaccumbens dopaminergic projections (Benoit-Marand et al 2000;Dugast et al 1994;Lester et al 2008Lester et al , 2009Schönfuß et al 2001;Suaud-Chagny 2004). Confirmation of the chemical specificity of our amperometric measurements has been provided by previous studies (e.g., Lee et al 2006;Mittleman et al 2008), showing that systemic administration of the selective DA reuptake inhibitor nomifensine significantly increases electrical stimulation-evoked DA oxidation current and delays recovery to prestimulation baseline levels.…”
Section: Da Functional Dynamicsmentioning
confidence: 69%
“…Rather, our results demonstrate that VTA AChR blockade is sufficient to induce a behavioral response consistent with an antidepressant-like effect. Given the recent evidence for a causal role of phasic DA activity in the VTA to NAc pathway in depressive-like behavior [14, 15] and the ability of VTA nAChR or mAChR blockade to reduce phasic DA release in the NAc [16, 19, 20, 54, 55], it is possible that our observed decrease in immobility is mediated by the ability of the AChR antagonists to decrease phasic DA release in the NAc. Indeed, previous studies have also revealed alterations in phasic DA activity in preclinical genetic and behavioral models of depression [11, 12, 5658].…”
Section: Discussionmentioning
confidence: 98%
“…However, several findings have lead to the suggestion that the glutamate projection from the LDT to the VTA, while involved, does not play a key role in control of the LDT of burst firing of DA neurons necessary for the large efflux of DA within the mesoaccumbal pathways associated with development of drug dependency. Efflux of DA within the nAcc elicited by stimulation of the LDT was blocked if muscarinic and nicotinic cholinergic receptor inhibitors were present in the VTA suggesting a major role of ACh in control of DA VTA cell firing [174]. Glutamate microinfusion within the VTA of LDT-inactivated animals, while it did significantly increase firing rate of DA cells, it failed to restore burst firing of DA neurons [87].…”
Section: The Role Of Noncholinergic Ldt-vta Pathways In Drug Addimentioning
confidence: 99%